Sources of air pollution in a region of oil and gas exploration downwind of a large city. (November 2015) - Rutter, Andrew P.; Griffin, Robert J.; Cevik, Basak Karakurt; Shakya, Kabindra M.; Gong, Longwen; Kim, Saewung; Flynn, James H.; Lefer, Barry L.
Abstract: The air quality in the outflow from Fort Worth, TX was studied in June 2011 at a location surrounded by oil and gas development in the Barnett Shale. The objectives of this study were to understand the major sources of volatile organic compounds (VOCs) and organic aerosols and explore the potential influence each VOC source had on ozone and secondary organic aerosol formation. Measurements of VOCs were apportioned between six factors using Positive Matrix Factorization (PMF): Natural Gas (25 ± 2%; ±99% CL); Fugitive Emissions (15 ± 2%); Internal Combustion Engines (15 ± 2%); Biogenic Emissions (7 ± 1%); Industrial Emissions/Oxidation 1(8 ± 1%); and Oxidation 2 (18 ± 2%). Reactivity calculations suggest the Biogenic and Oxidation 2 factors were the most likely VOC sources to influence local ozone. However, enough OH reactivity was calculated for factors related to the oil and gas development that they could incrementally increase O3 . Three organic aerosol (OA) types were identified with PMF applied to high-resolution time-of-flight aerosol mass spectrometry measurements: hydrocarbon-like OA (HOA; 11% of mass) and two classes of oxidized OA (semi- and less-volatile OOA, SV and LV; 45% and 44%, respectively). The HOA correlated with the Internal Combustion Engine VOC factor indicating that a large fraction of the HOA was emitted by gasoline and diesel motors. The SV-OOA correlated with the oxidized VOC factors during most of the study, whereas a correlation between LV-OOA and the oxidized VOC factors was only observed during part of the study. It is hypothesized that SV-OOA and the oxidized VOC factors correlated reasonably well because these factors likely were separated by at most only a few oxidation generations on the oxidation pathway of organic compounds. Highlights: 6 volatile organic carbon sources are resolved from autoGC and PTR-MS measurements. 3 organic aerosol classes are resolved from aerosol mass spectrometer measurements. Insights into the organic aerosol sources are gained from VOC sources. Reactivities suggest biogenic and oxidized VOCs contribute significantly to ozone. Reactivities suggest oil and gas emissions contribute incrementally to local ozone.